DRILLING OF OIL AND GAS BORE: YESTERDAY, TODAY, TOMORROW - Yaremiychuk, R. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
The article deals with development of bore drilling technologies over the past 150 years. Rotor drilling and drilling with turbo booms, electric drills, screw engines are analyzed. According to the author drilling operations of bores should consist of two parts the first of which provides maximum possible drilling speed, and the second – the proper disclosure of productive strata. When implementing the first and second parts of the project it is recommended to use service system for the implementation of certain types of work with the involvement of specialists of the profile. This applies in the first place to the regulation of the properties of washing liquids, the modes of their circulation in the well, and also the processes of fixing the walls of the well. According to the author service companies should also be involved in all types of recovery of filtration characteristics of reservoir layers.